Compartment-specific regulation of stromal differentiation of the spleen in health and disease - Chayeen Brotzki da Costa; Angéla Kecskés; Tibor Jánosi; Kata Váradi; Zoltán Kellermayer; Péter Balogh (Genes & Immunity, 2026)
Abstract Peripheral lymphoid organs in mammals are highly organized, complex tissues that support adaptive immune responses. In terms of comparative developmental biology, the mobile leukocytes of shared hematopoietic lineages in the spleen, lymph nodes, and mucosal lymphoid tissues perform similar functions during antigen recognition and intercellular communication, indicating them as largely homologous. However, the sessile stromal elements within these tissues that create preferential lodging domains for leukocytes differ considerably in their developmental features and structural organization, appearing analogous rather than homologous. Recent studies of splenic stromal architecture have identified region-specific transcription factors, chemokine signatures, and cell surface molecules that guide the specialization of the red pulp and marginal zone, two compartments unique to the spleen. This review—with particular emphasis on Nkx family members as key morphogens regulating spleen development and function—summarizes the roles of critical transcription factors in stromal differentiation pathways, architectural features, and immunological processes under both physiological and pathological conditions.